The Efficacy of Rheum ribes L. Stalk Extract on Lipid Profile in Hypercholesterolemic Type II Diabetic Patients: A Randomized, Double-Blind, Placebo - Controlled, Clinical Trial - H Fallah Huseini; R Heshmat; F Mohseni; AH Jamshidi; SHR Alavi; M Ahvasi; B Larijani (Institue of Medicinal Plants, ACECR, 2008)
Background: Previous clinical and experimental studies suggested the valuable effect of some herbal medicines on hyperlipidemic profile. Rheum ribes an herbal medicine has been prescribed for the treatment of diabetes and hyperlipidemia by several herbalists in Iran. Objective: The present study was designed to investigate the efficacy of Rheum ribes stalk extract on lipid profile in hypercholesterolemic type II diabetic patients. Method: One month randomized double blind clinical trial was conducted on 36 hypercholesterolemic, type II diabetic patients, referred to Diabetic Clinic at Special Medical Center Tehran Iran. All the patients who participated were aged between 40 to 60 years had LDL cholesterol above 100 mg/dl and confirmed type II diabetes with fasting blood glucose above 150 -200 mg/dl. The patients were not taking any antihyperlipidemic drug during last one month and continue their standard anti-diabetic therapy without any change during the study. The patients were randomly allocated in two groups. One group received 1200 mg Rheum ribes daily in three 400 mg capsule and other received placebo similarly. The patients fasting blood glucose, total cholesterol, LDL, HDL cholesterol, triglyceride, creatinine, SGOT and SGPT were determined at the beginning and at the end of the study after one month. Results: At the end of the study in Rheum ribes treated patients fasting blood glucose, LDL and total cholesterol significantly decreased as compared to placebo treated patients as well as compared to beginning of the study. In placebo treated patients all blood level of biochemical determination at the end of the study were not significantly changed as compared to beginning of the study. Conclusion: Rheum ribes stalk extract treatment had beneficial effect on lipid as well as glucose profile in type II diabetic hypercholesterolemia patients without any adverse effect on liver and kidney.